DOES ENTREPRENEURIAL EDUCATION MATTER IN THE CULTIVATION OF BUSINESS ENTREPRENEURIAL INTENTIONS AND SOCIAL ENTREPRENEURIAL INTENTIONS? - John Kalu Osiri; Kenneth Kungu; Amarachi Amaugo; Jenesha Francis (Erudio Journal of Educational Innovation, 2020)
This study examines whether or not entrepreneurial education can predict business entrepreneurial intentions and social entrepreneurial intentions. This research draws primarily from the analysis of survey data of collegiate students as well as relevant literature in the field. In addition to entrepreneurial education, the effect of gender on entrepreneurial intentions was also examined. Results of this analysis can be used to foster increased entrepreneurial activities within the collegiate community.